Directives, expressives, and motivation - Toru Suzuki (Theoretical Economics, 2017)
When an agent's motivation is sensitive to how his supervisor thinks about the agent's competence, the supervisor has to take into account both informational and expressive contents of her message to the agent. This paper shows that the supervisor can credibly express her trust in the agent's ability only by being unclear about what to do. Suggesting what to do, i.e., 'directives,' could reveal the supervisor's 'distrust' and reduce the agent's equilibrium effort level even though it provides useful information about the decision environment. There is also an equilibrium in which directives are neutral in expressive content. However, it is shown that neologism proofness favors equilibria in which directives are double-edged swords.
Keywords: D83; 330; Communication games; directives; expressives; economics and language